Pengaruh Penguasaan Tecnological Pedagogical and Content Knowledge (TPACK) dan Microteaching terhadap Kesiapan Menjadi Guru dengan Kepercayaan Diri Sebagai Variabel Intervening pada Mahasiswa Pendidikan Administrasi Perkantoran Angkatan 2021 Fakultas Ekonomi Universitas Negeri Medan - Gabriella Simanjuntak; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to examine and analyze the influence of Technological Pedagogical and Content Knowledge (TPACK) and Microteaching on students’ readiness to become teachers, with self-confidence as an intervening variable, among Office Administration Education students of the 2021 cohort at the Faculty of Economics, Universitas Negeri Medan. The research employed a quantitative method using primary data collected through questionnaires and secondary data obtained from books, journals, and previous studies. The sample consisted of 88 respondents, with data analysis conducted using Path Analysis supported by SPSS software and Sobel Test. The results reveal that TPACK (β = 0.280; Sig. = 0.000) and Microteaching (β = 0.511; Sig. = 0.000) have a significant effect on self-confidence, with an R Square value of 0.572. Furthermore, TPACK (β = -0.481; Sig. = 0.000), Microteaching (β = 0.383; Sig. = 0.000), and self-confidence (β = 0.823; Sig. = 0.000) significantly affect readiness to become a teacher, with an R Square value of 0.785. The Sobel Test results indicate that self-confidence plays a significant mediating role in strengthening the influence of TPACK (Z = 3.534) and Microteaching (Z = 5.132) on readiness to become a teacher. Thus, this study implies that the combination of TPACK mastery, Microteaching, and self-confidence simultaneously enhances students’ readiness to undertake the teaching profession.